Instability of Structure Plates under Two-directional Compression - Žiliukas, A. (Elektronika ir Elektrotechnika, 2008)
For the perfect structures the peculiarities of deformability, strength and stability of plate form elements are very essential due to the security of accurate and reliability of performed functions. According to the studies of other authors, the poor attention is paid to the behaviour of materials in the case of complex loading. In these studies, the influence of both normal and shear stress acting in the same time is not evaluated. Whereas, it is very important for the investigation of elastic-plastic materials. In this study according to classical solutions in both the case of unidirectional and two-directional loading in the analogical way as in the case of strength criteria, the stability criterion is suggested. The influence of geometry is modelled in this study. This allows the covering all of the complex loading cases and the evaluating of the behaviour of the elastic-plastic materials. The analytical results are compared to experimental ones. Ill. 3, bibl. 13 (in English; summaries in English, Russian and Lithuanian).